Cryptosporidium infections of ring-necked pheasants (Phasianus colchicus) from an intensive artificial breeding programme in the Czech Republic - Máca, Ondřej; Pavlásek, Ivan (Parasitology research, 2016)
From July to November 2012, preliminary coprological examinations were carried out on 85 pooled faecal samples of different aged ring-necked pheasants (Phasianus colchicus) (hatches from May until July) from an intensive artificial breeding programme in the Czech Republic. Cryptosporidium oocysts were detected in 12 samples (14.1 %) of ages >12 weeks (August-September). These results were supported by findings of Cryptosporidium baileyi and Cryptosporidium meleagridis oocysts in intestinal, or cloacal contents, and/or the bursa of Fabricius in 9 from 36 examined dead pheasants (prevalence 25 %). We describe in detail the various age groups of pheasants after hatching and present graphically the overall results of coprological examinations, showing pathways of infection of C. baileyi and C. meleagridis during the full rearing seasons of 2013 and 2014. We found very similar mean proportions of Cryptosporidium-positive samples over the entire 2013 period in pheasantry (173 pooled samples tested, 25 positive, 14.5 %) and 2014 (238 samples tested, 43 positive, 18.1 %). All tests were verified as being Cryptosporidium positive in 9 from 219 (prevalence 4.1 %) and 4 from 168 (prevalence 2.4 %) post-mortem examinations. Significantly, C. baileyi was found more frequently in faeces, with positivities ranging from 11.1 to 100 % (4->16-week-old pheasants). Oocysts of C. meleagridis were detected at ages 6->15 weeks ranging from 7.1 to 100 % in faeces during the rearing seasons. The burdens of C. baileyi (7 of 14 and 10 of 16) and C. meleagridis (5 of 14 and 7 of 16) for each year, in monitored brooder houses, flight pens and spread across all open areas were recorded. Oocysts of C. baileyi and C. meleagridis obtained from this study, and Cryptosporidium galli (obtained in another aviary from 36-week-old pheasants), were sequenced, and we characterized the highly variable 60-kDa glycoprotein gene of C. meleagridis. These results highlight the real risk of transmission of Cryptosporidium to susceptible wild birds and other potential hosts after termination of rearing and release.
Keywords: Poultry Diseases; Feces; C. baileyi; střeva; Aging; oocysty; Galliformes; kryptosporidióza; Česká republika; Cryptosporidiosis; Cryptosporidium meleagridis; GP60; Czech Republic; nemoci drůbeže; Oocysts; Animals; zvířata; Prevalence; stárnutí; Dynamics and transmission; Cryptosporidium; Intestines; C. galli; feces